KAWASAN WISATA PANTAI SINAM DI KECAMATAN PEMANGKAT - Muliadi, Muliadi; Caesariadi, Tri Wibowo; Khaliesh, Hamdil (JMARS: Jurnal Mosaik Arsitektur, 2022)
Sambas Regency is an area that has a coastal area stretching from the Semelagi area to the Temajuk Coast region which borders Malaysia. Sinam Beach is one of the tourist attractions, precisely in Pemangkat District. The beach is often visited by tourists on weekends for recreation and relaxation. This Sinam Beach Tourism Area is very worrying because natural disasters often occur in the form of tidal floods, strong winds and coastal abrasion, the inability of the community and local government to utilize and manage existing potentials optimally to create tourist attractions. The purpose of this design is to produce a plan and design for the Sinam Beach Tourism Area in Pemangkat District which can meet the needs of tourists and utilize the potential of natural resources.The concept used is green open space by the beach. The method used in the design is to find ideas, collect data and analyze data. The design of the Sinam Beach Tourism Area creates a tourist zone, namely land tourism, water tourism and mangrove tourism.. Supporting facilities in the design are a tourist information center,management office, public toilets, promenade, floating restaurant and UMKM area.